Home Ownership Loan Agreement in the Labuha Branch of Bank Syariah Indonesia - Budiono, Arief; Faisal, Fatma; Hasim, Dahlai (Jurnal Ius Constituendum, 2025)
In this paper, the authors will analyze: (1) the details of the home ownership loan agreement in the Labuha Branch of Bank Syariah Indonesia (The Indonesian Sharia Bank/BSI) and (2) how to resolve the issue of default carried out one of the parties in the home ownership loan agreement in the Labuha Branch of BSI. Members of society who wish to own a home but lack funds may utilize the credit facilities provided by BSI by making a credit agreement (home ownership loan). It is one of the solutions for prospecting housing consumers to quickly have a house. This paper is urgent because the increasing Indonesian population leads to an increase in demand for housing. Banks like BSI can help society obtain house ownership loans amid the increasing house prices. This paper employed the normative empirical legal research method. Results showed that the agreement carried out by the debtor and creditor is already according to the applicable regulations. It was shown that there was an increase in the number of debtors who obtained home ownership loans from the Labuha Branch of BSI. In total, 83 debtors obtained such facilities from 2021 to 2023. In the case of problematic debtors, ten debtors experienced a default in the Labuha Branch of BSI from 2021 to 2023. In the case where debtors fail to carry out their obligations in paying installments or in repaying their debt, then the bank will sell the collateral object or the house.